Clinical characteristics of multiple sclerosis in the Tomsk region - V M Alifirova (Nevrologiâ, Nejropsihiatriâ, Psihosomatika, 2012)
Two hundred and eighty patients (102 men and 178 women; mean age 38.8ё0.7 years) with multiple sclerosis (MS) were examined to study its clinical picture in the Tomsk Region. There was a preponderance of patients have with remitting MS whereas primarily progressive MS was rarest. The bulk of the patients had moderate neurologic deficit and moderate disease progression. The women were observed to exhibit a more favorable course of MS, which manifested itself as less severe neurological deficit and slower disease progression.